P75NTR Exacerbates SCI-induced Mitochondrial Damage and Neuronal Apoptosis Depending on NTRK3 - Tan, Wei; Dong, Longjia; Shi, Xuexing; Tang, Qian; Jiang, Dianming (Current Neurovascular Research, 2021)
Objective: The aim of the study was to investigate the mechanism by which p75 neurotrophin receptor (p75NTR) affects mitochondrial damage and neuronal apoptosis in spinal cord injury (SCI). Methods: After the establishment of SCI rat models, short hairpin (sh) RNA of p75NTR and control sh-RNA were injected into SCI rats, respectively. On days 1, 7 and 21 after SCI, the severity of SCI and cell apoptosis in SCI rats were determined as well as the recovery of hind limb performance and p75NTR expression. After spinal cord neurons were transfected with p75NTR overexpression plasmid or empty plasmid vector or cotransfected with overexpression plasmids of p75NTR and neurotrophic tyrosine receptor kinase3 (NTRK3), the expression levels of p75NTR and NTRK3 were quantified. Moreover, we detected the apoptosis and proliferation rates of the neurons in addition to the levels of reactive oxygen species (ROS) and mitochondrial membrane potential (MMP) in the neurons. The binding between p75NTR and NTRK3 was confirmed via Co-immunoprecipitation (Co-IP). Results: The rat spinal cords in the Model group were notably damaged after SCI accompanied by increased apoptosis and decreased locomotor function. The expression of p75NTR was significantly upregulated after SCI. The aforementioned injuries were remarkably ameliorated in response to injection of sh-p75NTR. p75NTR overexpression induced mitochondrial damage and neuronal apoptosis in spinal cord neurons, while the promotive effects were perturbed by NTRK3 overexpression. Furthermore, p75NTR directly bound to and downregulated NTRK3. Conclusion: Both in vivo and in vitro experiments showed that p75NTR aggravates mitochondrial damage and neuronal apoptosis in SCI through downregulating NTRK3.
Keywords: mitochondrial damage